Editorial: Pruritus medicine - Ständer, Sonja; Sun, Yan-Gang; Schmelz, Martin (Frontiers in medicine, 2021)
Mental factors are important for itch perception and its progression. K. Lüßmann and coauthors describe that itch intensity and certain facets of mindfulness were associated with itch catastrophizing in AD patients https://doi.org/10.3389/fmed.2021.627611 . On the other hand, distraction might help to reduce itch as investigated by van Laarhoven et al. by training volunteers to reduce attention towards itch https://doi.org/10.3389/fmed.2021.627593 . Pruritus is a subjective symptom without objective measurement. Accordingly, patient reported outcomes are still the gold standard in the assessment of the course. However, the complex process of international harmonization and validation is still ongoing. Stępień and Reich contribute to this topic by framing severity levels in a novel questionnaire https://doi.org/10.3389/fmed.2020.614005 .In sum, this collection of articles combines several up to date aspects of the neurobiology and clinics of pruritus, including also new methods and innovative concepts in itch research.
Gesehen am 15.12.2021